Design and Fabrication of a Low-Cost System for Smart Home Applications - Ammar Ali Sahrab; Hamzah M. Marhoon (Universitas Muhammadiyah Yogyakarta, 2022)
Smart systems and security got impressive attention and development in recent years, which have been appeared in the terms of smart homes, intelligent security, and the Internet of Things (IoT). Home automation comprises the controlling of the electrical appliances in the home wirelessly or automatically. Many different integrated circuits, sensors, modules, and embedded systems are available to be compatible to integrate with smart homes. In order to apply the concept of smart homes, many issues should be considered like as providing a user-friendly, reliable, secure, and cost-effective. In this paper, an effective and low-cost smart home system is designed and implemented based on the Arduino microcontroller boards with its compatible modules. The proposed work employed many types of sensors to carry out the tasks for the smart home for a couple of the essential segments, the first one is home security and the latter one is home automation. The antitheft home segment is based on the laser source directed on the light-dependent resistor and infrared sensor; once the thief tries to cut the laser or passes beside the sensor, the alarm will be switched on. The later segment aims to detect the fire occurring by the means of the flame sensor, gas leakage detection by the MQ-05 sensor, servo motor to opening/closing the garage door, LCD to display the status of the all-utilised sensors, and finally, the Bluetooth module to controlling the garage door wirelessly. To increase the system performance and reliability the Arduino Nano and the Arduino Leonardo board are utilised.